Handbook of Plant Biotechnology 2004
DOI: 10.1002/0470869143.kc025
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism

Abstract: The yield from crop plants has been subject to improvement through conventional breeding and modifications in agricultural practice for many decades. More recently, the use of molecular genetic approaches has allowed more directed approaches towards crop improvement. Specific examples of both successful strategies and of fundamental knowledge gleaned from unsuccessful strategies are presented including manipulations of starch, sucrose and novel sugar content. The utility of metabolic control analysis in the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 260 publications
0
6
0
Order By: Relevance
“…This finding is of great importance with respect to attempts to breed crops with improved chemical composition, since many attempts to metabolically engineer plants to produce elevated levels of a given metabolite were able to meet this goal, but only at the cost of compromising yield (Fernie and Willmitzer, 2004;Van Camp, 2005). Evaluation of the trait network of the heterozygous ILHs revealed that morphological parameters were less tightly associated to metabolic traits than they were in the homozygous IL population and, furthermore, that while a minority of metabolites were clearly morphogically associated in both populations, the majority appeared to be linked only in the homozygous ILs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is of great importance with respect to attempts to breed crops with improved chemical composition, since many attempts to metabolically engineer plants to produce elevated levels of a given metabolite were able to meet this goal, but only at the cost of compromising yield (Fernie and Willmitzer, 2004;Van Camp, 2005). Evaluation of the trait network of the heterozygous ILHs revealed that morphological parameters were less tightly associated to metabolic traits than they were in the homozygous IL population and, furthermore, that while a minority of metabolites were clearly morphogically associated in both populations, the majority appeared to be linked only in the homozygous ILs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is only recently that these studies have largely focused on single, or at most, a handful, of metabolites, such as carotenoid content in tomato (Liu et al, 2003a), protein content in maize (Zea mays) (Moose et al, 2004), starch content in potato (Solanum tuberosum) and rice (Oryza sativa) (Fernie and Willmitzer, 2004), and tocopherol levels in Arabidopsis (Gilliland et al, 2006). Over the last few years, however, pathway-based approaches have began to be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the role of FK has been the subject of intensive recent investigation in the closely related species tomato (Solanum lycopersicum; Kanayama et al 1997, Odanaka et al 2002, German et al 2003, the profound differences in metabolism in these species (see Fernie and Willmitzer 2004 for details) led us to address the role of FK in potato. For this purpose, we generated transgenic potato plants in two cultivars of potatoRecord and Desiree that expressed StFK1 in both the sense and antisense orientation.…”
Section: Genetic Manipulation Of Stfki In Potato Plantsmentioning
confidence: 99%
“…Diurnal regulation of plant metabolism has been studied for many years with particular attention paid to carbohydrates such as sucrose and starch (Geiger and Servaites 1994;Kruger 1997;Fernie and Willmitzer 2004) and to important components of carbon-nitrogen interaction such as 2-oxoglutarate, glutamate and asparagine (Ferrario-Mery et al 2001;Stitt and Fernie 2003;Masclaux-Daubresse et al 2002). Important regulatory mechanisms such as the fructose 2, 6-bisphosphatemediated feedforward and feedback regulation of sucrose synthesis have been uncovered (see Stitt 1990;Winter and Huber 2000).…”
Section: Introductionmentioning
confidence: 99%